A Trajectory of Long-Term Antipsychotic Medication Dosage in Inpatients with Severe Behavioral and Psychological Symptoms of Dementia: A Retrospective Study - Tada, Teruo; Suzuki, Takefumi; Iwata, Yusuke; Kubota, Masaharu; Watanabe, Koichiro; Sakurai, Hitoshi (Pharmacopsychiatry, 2024)
Introduction While antipsychotics are often prescribed for behavioral and psychological symptoms of dementia (BPSD), typically on an off-label basis, these medications have serious adverse effects. This study investigated the long-term use of antipsychotics among inpatients with dementia displaying severe BPSD, focusing on how prescriptions change over time.Methods Medical charts at Kusakabe Memorial Hospital were retrospectively reviewed from October 2012 to September 2021. The study included patients diagnosed with dementia, admitted for BPSD, and were continuing antipsychotics at 3 months of their admission. Antipsychotic dosages were categorized as high (≥300 mg/d), medium (100–300 mg/d), and low (<100 mg/d) based on chlorpromazine equivalents and tracked until 15 months during hospitalization. Binary logistic regression was used to identify factors associated with dosage reductions between months 3 and 6.Results This study involved 188 patients, with an average age of 81.2 years, 67% of whom were diagnosed with Alzheimer's dementia. At 3 months, 15.4% were taking high, 44.1% on medium, and 40.4% on low dosages of antipsychotics. The highest average dosage was observed at 3 months, with a subsequent decrease over time. By the 12th month, 20–30% of patients in all dosage categories had stopped their antipsychotic medication. Significant factors for dosage reduction included higher initial doses (OR 1.003, 95%Cl: 1.001–1.006, P=0.01) and male gender (OR 2.481, 95%Cl: 1.251–4.918, P=0.009).Discussion A trajectory of antipsychotic dosage in inpatients with severe BPSD has rarely been reported. This research emphasizes the need for personalized strategies in managing long-term pharmacotherapy for this vulnerable group of patients.
Keywords: antipsychotics; behavioral and psychological symptoms of dementia; dose; hospitalization; long-term